Attendance zones in the suburbs. (February 2023) - Asson, Sarah; Frankenberg, Erica; Fowler, Christopher S.; Buck, Ruth Krebs
While suburban schools across the country have become increasingly racially and economically diverse in recent decades, many remain highly segregated. School attendance zone boundaries (AZBs) play a critical role in shaping these patterns of within-district segregation. AZBs are especially important in suburban areas with growing and diversifying student populations. Using novel, longitudinal AZB data dating back to 1990, authors Sarah Asson, Erica Frankenberg, Christopher Fowler, and Ruth Krebs Buck studied the relationship between AZBs and segregation over time in three large suburban districts. They found AZB changes have not yet been realized as a force for desegregation. To do so will require more explicit action prioritizing racial and economic diversity .